THE APPLICATION OF CLASSICAL MUSIC THERAPY TO IMPROVE SLEEP QUALITY IN PRE-BIOPSY PATIENTS AT THE WEST PADMANABA WARD OF DR. SARDJITO GENERAL HOSPITAL IN YOGYAKARTA - Fahita Aulia Mudmandiah; Sumarti Endah Purnamaningsih Maria Margaretha (Jurnal Kesehatan Karya Husada, 2025)
Background : Surgery is a medical procedure performed by cutting or opening certain body parts. Sleep disturbance is a common problem often experienced by preoperative patients due to anxiety, pain, and discomfort before undergoing a surgical procedure. Non-pharmacological therapy such as classical music therapy can be an effective alternative to improve sleep quality. Objective : To describe the application of classical music therapy in improving sleep quality in preoperative patients in the Padmanaba Barat Ward of Dr. Sardjito General Hospital, Yogyakarta. Method : The research used is a descriptive case study of one preoperative patient who experienced sleep disturbance. The intervention was carried out by providing classical music therapy for 15-30 minutes before going to bed for five consecutive days. Sleep quality was measured using the Pittsburgh Sleep Quality Indeks (PSQI) before and after the intervention. Results : Shows a gradual increase in sleep quality from a PSQI score of 13 to 5, indicating an improvement from moderate to good sleep quality. Conclusion : from this study is that classical music therapy has been proven effective in improving the sleep quality of preoperative patients and can be used as one of the non-pharmacological interventions in nursing services.